El delito de femicidio viola el bien jurídico protegido por el estado. - Jaramillo Haro, Karina del Roció (2016)
Violence against women has become a problem that affects everyone, an issue that has always been and often publicly, however, in most cases, it has been reduced to the private or domestic sphere. Gender-based violence is deadly, women are exposed to specific forms of risk to their bodily, psychological and emotional integrity. Therefore, it is necessary to encourage the use of a new concept to describe the murder of a woman when it is committed due to the gender of the victim. And it is necessary, at the same time, to modify the Penal Code to sanction the mobile based on the gender that characterizes the corporal integrity. With the new conquests in the International Law of Human Rights, violence against women is already considered as a serious violation of their human rights, along with this a worldwide trend has been developed to denounce extreme violence against women as femicide. Therefore, in this research work entitled "The crime of femicide violates the legal right protected by the State", is proposed as an alternative to reduce violence against women and femicide in Ecuador, the increase in the penalty of imprisonment that is established in Art. 141 of the Integral Organic Penal Code from 22 to 26 years, to 28 years of major prison as a policy model for the prevention of gender violence, in this case, homicide. Keywords: Crime, femicide, rape, legally, State punishment.